Measuring Job Crafting Across Cultures: Lessons Learned From Comparing a German and an Australian Sample - Schachler, Vivian; Epple, Sandra D.; Clauss, Elisa; Hoppe, Annekatrin; Slemp, Gavin R.; Ziegler, Matthias (Frontiers in Psychology, 2019)
Job crafting refers to the act of employees actively altering work aspects to better suit their values and interests. Slemp and Vella-Brodrick (2013) proposed a Job Crafting Questionnaire (JCQ) in English consisting of three facets: task crafting, cognitive crafting, and relational crafting. This is in line with the original conceptualization of job crafting by Wrzesniewski and Dutton (2001). However, there has not yet been an evaluated German translation of this measure. Therefore, this paper aims at evaluating the psychometric properties of scores from a German translation of the JCQ, using the original Australian dataset and a German sample of 482 employees. Our findings showed first evidence for the reliability and validity of the scores. We also extend prior research and include creative self-efficacy in the nomological network of job crafting. Importantly, strong factorial measurement invariance was demonstrated, allowing for comparisons between the job crafting scores of German- and English-speaking samples. Based on this example, we highlight the importance of enriching measurement invariance tests by including other key constructs. Our results suggest that the German JCQ is an acceptable tool for measuring job crafting, as originally conceptualized by Wrzesniewski and Dutton (2001).